2019
DOI: 10.3991/ijet.v14i22.11741
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Documents Published in the Web of Science Database on Teachers' Gamification Method: A Content Analysis

Abstract: Gamification is the use of game design elements in non-game contexts and it is gaining momentum in a wide range of areas including education. Despite increasing academic research exploring the use of gamification in education, little is known about teachers' main drivers and barriers to using gamification in their courses. Through the search conducted on Web of Science database with the keywords "teacher” and “gamification", the study is based on the analysis of the documents published. All articles published… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…In [44], the researchers employed behavioural, cognitive and emotional engagement factors to study student engagement concerning gamified online discussions, while in [74], the roles of emotional, cognitive, and behavioural aspects of student engagement in online e-learning were studied. Likewise, in [75], the researchers have used effective, behavioural, and cognitive aspects to study student engagement with gamified e-learning activities, while in another study, the researchers discussed the emotional, social, and behavioural factors underlying student engagement with a gamified e-learning platform [76,77]. The summary of the reviewed researches against the type of engagement factors are depicted in Table 4.…”
Section: Student Engagement Factorsmentioning
confidence: 99%
“…In [44], the researchers employed behavioural, cognitive and emotional engagement factors to study student engagement concerning gamified online discussions, while in [74], the roles of emotional, cognitive, and behavioural aspects of student engagement in online e-learning were studied. Likewise, in [75], the researchers have used effective, behavioural, and cognitive aspects to study student engagement with gamified e-learning activities, while in another study, the researchers discussed the emotional, social, and behavioural factors underlying student engagement with a gamified e-learning platform [76,77]. The summary of the reviewed researches against the type of engagement factors are depicted in Table 4.…”
Section: Student Engagement Factorsmentioning
confidence: 99%
“…As information-communication technology (ICT) has been blurring the line between formal, non-formal, and informal education, game-based learning and gamification have become interesting approaches to improve outcomes outside the traditional gaming context, such as students' motiva-tion, engagement, and performance. The number of publications on gamification in education has indeed been steadily growing in the last decade but focused mainly on its design principles and results [1], [2]. However, years of research on technology acceptance have shown the leading role of personal characteristics in predicting the adoption of pedagogical innovations [3], [4].…”
Section: Introductionmentioning
confidence: 99%
“…As evidenced by the pre-mentioned studies and recent reviews of gamification in education [6], [11], [12], [28], several issues can be identified. First, gamification still requires more careful experimental evaluations to investigate its effect on learning since most studies focus on short-term learning with limited sample sizes.…”
Section: Related Workmentioning
confidence: 99%
“…Fourth, mixed findings were generated for different cultures, learning environments and the use of single or combined game elements. According to these issues, there is a research gap in conducting a more focused research study on the effect of gamification on young students applied in a different culture and application domain [28]. To the best of our knowledge, the study presented in this paper is one of the first careful studies that examine the impact of gamification on elementary school students applied to Arabic language learning.…”
Section: Related Workmentioning
confidence: 99%